2019
DOI: 10.1017/ice.2018.356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing urine testing orderables and clinician order sets on inpatient urine culture testing: Analysis from a large academic medical center

Abstract: Objective: To evaluate the impact of changes to urine testing orderables in computerized physician order entry (CPOE) system on urine culturing practices. Design: Retrospective before (January 2015 to April 2016) and after (May 2016 to August 2017) study. Setting: A 1,250-bed academic tertiary referral center. Patients: Hospitalized adults who had ≥1 urine culture performed during their stay. Intervention: The intervention (implemented in April 2017) consisted of notifications to providers, changes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…Other investigators have found similar findings for cardiac enzyme testing and suggested that unnecessary duplicative orders occurred more frequently when patients were transferred from the emergency department to inpatient units (16). The role of computerized physician order entry (CPOE) systems in altering physician ordering practices to reduce unnecessary laboratory testing has been well described (3,8,17). A computerized pop-up alert screen with pending results and the most recent completed test result with the date has resulted in a significant reduction in duplicate orders for ordering of panels of tests for acute hepatitis (17).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Other investigators have found similar findings for cardiac enzyme testing and suggested that unnecessary duplicative orders occurred more frequently when patients were transferred from the emergency department to inpatient units (16). The role of computerized physician order entry (CPOE) systems in altering physician ordering practices to reduce unnecessary laboratory testing has been well described (3,8,17). A computerized pop-up alert screen with pending results and the most recent completed test result with the date has resulted in a significant reduction in duplicate orders for ordering of panels of tests for acute hepatitis (17).…”
Section: Discussionmentioning
confidence: 87%
“…In this study, patients who had an index culture of a sample from an indwelling catheter had a lower risk of having an inappropriate repeat urine culture than those who had an index culture of clean-catch/straight catheterized and procedural specimens. This finding could potentially be explained by our institutional intervention of modifying urine testing order sets in the CPOE system, which was implemented in April 2016 (8). Urinalysis parameters of proteinuria and blood in the urine were excluded from reflex urine culture testing, with the exception of testing for neutropenic patients (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations